Building direction dependence of corrosion resistance property of Ti–6Al–4V alloy fabricated by electron beam melting - Gong, Xiaojuan; Cui, Yujie; Wei, Daixiu; Liu, Bin; Liu, Ruiping; Nie, Yan; Li, Yunping (Corrosion Science, 2017)
•Electrochemical measurements of EBM Ti–6Al–4V alloy were carried out.•Corrosion resistance in 1 M HCl solution is different along building direction.•Grain boundary and β phase along building direction account for the difference. Electrochemical measurements in 1 M HCl solution were performed to investigate the corrosion behaviour of Ti–6Al–4V alloy fabricated by electron beam melting (EBM) with cylindrical axes deviating from the building direction by 0°, 45°, 55°, and 90°. Microstructure characterization before and after the tests was carried out by using a variety of methods The results suggested that the corrosion resistance of EBM alloy in 1 M HCl solution increased slightly in the order of 45°, 90°, 55°, and 0°. Such difference can be ascribed to the grain boundary density and β phase constitution, which varied with the building direction.